Exercise Addiction and Muscle Dysmorphia: The Role of Emotional Dependence and Attachment - Olave, Leticia; Estévez, Ana; Momeñe, Janire; Muñoz-Navarro, Roger; Gómez-Romero, María José; Boticario, María Jesús; Iruarrizaga, Itziar (Frontiers in Psychology, 2021)
Background: Both exercise addiction (EA) and muscle dysmorphia (MD) primarily involve compulsive practice of physical exercise and are classified as behavioral addictions in different lines of research. These types of addictions are frequently comorbid with other addictive pathologies, such as emotional dependence (ED), which is closely related to childhood attachment. This study is presented to address the scarcity of research relating EA and MD with other behavioral addictions. The aims are: analyze the sex differences found in emotional dependence, attachment dimensions, EA and MD; analyze the association between EA and MD and other behavioral addictions, such as emotional dependence and attachment dimensions; and analyze the possible role that childhood attachment plays in mediating the interaction between emotional dependence and EA and MD. Method: The sample comprised 366 participants (54.6% women) aged 17-31 (M = 23.53; SD = 6.48). Results: There are sex differences, with men scoring higher in EA, MD and ED. The positive relationship between EA and ED (values between .16 and .28), MD (presenting values between .42 and .70) and attachment styles based on preoccupation, interference, permissiveness and value of parental authority (values between .11 and .14) is highlighted. On the other hand, MD was positively related to ED (values ranging from .24 to .36) and attachment styles based on value of parental authority, self-sufficiency and resentment against parents (between .17 and .18), and negatively related to secure attachment (values between -.13 and -.18). Likewise, the predictive role of ED and attachment styles on EA and MD was tested. And it was observed how attachment styles mediated the relationship between EA and ED, as well as the relationship between MD and ED. Thus, it has been shown that people with EA and MD present attachment styles that may influence negatively the decision-making process when choosing inappropriate strategies to achieve adequate emotional regulation, even selecting inappropriate goals for physical exercise with negative consequences.. Conclusions: the dissemination of the findings among mental health and sports science professionals is necessary to develop prevention and intervention strategies for people affected by EA and MD.